Effect of Culinary Processes on the Content of Nitrates and Nitrites in Potatoe - Mozolewski, Waclaw; Smoczynski, Stefan (Pakistan Journal of Nutrition, 2004)
The effect of potato culinary processing on the changes in the content of nitrates and nitrites was determined. The experimental material were potato tubers of Ibis, Mila and Muza varieties with elevated nitrate (175.4 - 250.7 mg NO3 • kg-1) and nitrite (1.7 - 4.3 mg NO2 • kg-1) content. The losses of nitrites occurring after the preliminary processing (washing, manual peeling and rinsing) were greater than nitrates and ranged from 25 to 75% and from 18 to 40%, respectively. Differences in the losses of these compounds were variety-dependent. During thermal processing of potato tubers with different methods, the losses of these compounds varied and were significantly greater for nitrites (61-98%) than for nitrates (16-62%). The greatest decrease in the content of nitrates was found for deep fried potatoes and for boiling in water. The losses of nitrates are significantly higher in peeled potato tubers subjected to thermal processing with direct contact of the product with water (p=0.05) than in steam or oil.